Rancang Bangun Sistem Informasi Anime Premium dan Non Premium Berbasis Web Dengan Menggunakan Metode Waterfall - Pasaribu, Nova Tresia; Masrizal, Masrizal; Harahap, Syaiful Zuhri (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Anime is a form of Japanese animation that can be created in the traditional way using hand drawing or using computer technology. Anime was introduced in Indonesia in the 1970s, but its popularity only increased in the 1990s after the airing of Doraemon on television stations. With the advancement of Information Technology, the spread of Anime is expanding. The availability of the internet allows viewers to enjoy Anime in streaming, so Anime can be accessed by anyone, anytime, and anywhere according to the wishes of the audience. Currently, Anime has experienced significant progress when compared to the past. Therefore, a number of people consider it more artistic in nature compared to Anime in the previous period. It should be noted that the images in Anime have become more proportional, colors are better, and the presence of HD (High Definition) technology improves the quality of the video, making it more interesting and understandable. Along with the spread of Anime through online platforms, audience interest in exploring various Anime has also increased, so a website-based information system is needed. Therefore, it is necessary to design and build an information system that is able to provide comprehensive access to various types of Anime, both Premium and non-Premium, in an integrated manner. An appropriate method of designing and building software is needed to ensure that this information system can meet the needs of users effectively. One method that can be used is the Waterfall method.